2014
DOI: 10.5194/cp-10-2053-2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ordovician paleogeography on the (in)stability of the climate

Abstract: Abstract. The Ordovician Period (485-443 Ma) is characterized by abundant evidence for continental-sized ice sheets. Modeling studies published so far require a sharp CO 2 drawdown to initiate this glaciation. They mostly used nondynamic slab mixed-layer ocean models. Here, we use a general circulation model with coupled components for ocean, atmosphere, and sea ice to examine the response of Ordovician climate to changes in CO 2 and paleogeography. We conduct experiments for a wide range of CO 2 (from 16 to 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 58 publications
(116 reference statements)
3
35
0
Order By: Relevance
“…However, the details of the coastlines in the paleogeographies are uncertain, in particular for greenhouse climates (Sømme et al, 2009). Furthermore, the nonlinearity found in our simulations supports previous studies that found that past climate sensitivity was a function of baseline CO 2 (e.g., Pohl et al, 2014, for the Ordovician) and suggests that further nonlinear behavior would occur if we carried out simulations at ×1 or ×8 CO 2 .…”
Section: Quantitative Role Of Nonlinear Feedbacks In Determining Climsupporting
confidence: 88%
“…However, the details of the coastlines in the paleogeographies are uncertain, in particular for greenhouse climates (Sømme et al, 2009). Furthermore, the nonlinearity found in our simulations supports previous studies that found that past climate sensitivity was a function of baseline CO 2 (e.g., Pohl et al, 2014, for the Ordovician) and suggests that further nonlinear behavior would occur if we carried out simulations at ×1 or ×8 CO 2 .…”
Section: Quantitative Role Of Nonlinear Feedbacks In Determining Climsupporting
confidence: 88%
“…The Late Ordovician (445 Ma, Hirnantian stage) setup of the model is fully described elsewhere (32). The model is driven by existing Late Ordovician climate simulations (31), conducted at a range of different atmospheric CO 2 and O 2 concentrations. Initially, we assume atmospheric O 2 = 0.6 PAL (∼14 vol.%) at 445 Ma, which is consistent with COPSE model simulations (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Because the location and depth of Ordovician ocean ridges are not well constrained, they are not included in the model. We use a flat-bottom ocean, the depth of which is set to present-day mean seafloor depth, that is À4000 m (Pohl et al 2014). The flat bottom is not expected to constitute a major bias.…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%
“…These more reliable global palaeogeographical reconstructions have allowed the formulation of simple conceptual and more complex numerical models for ancient atmospheric and ocean circulation patterns, or to hypothetically locate upwelling zones (e.g. Wilde 1991;Christiansen & Stouge 1999;Herrmann et al 2004;Pohl et al 2014;Servais et al 2014). More recently, new constraints on the palaeobiogeography of marine living communities were provided by the publication of maps showing much more precisely the ocean surface circulation modelled at various atmospheric CO 2 levels during the Early, Middle and Late Ordovician (Pohl et al 2016b).…”
mentioning
confidence: 99%